Optimal units of selection – how many plants are representative of diversity in collections of cowpea landrace accessions? - Hearne, Sarah Jane; Franco, J.; Magembe, E. (International Institute of Tropical Agriculture, 2010)
The International Institute of Tropical Agriculture houses the largest collection of cowpea landraces in the world. This collection has been studied using agro morphological, botanical and geographic descriptors to define a core collection with a smaller reference collection being defined thereafter using molecular markers. Within any collection of germplasm it is important to understand the level of inbreeding and heterogeneity as these have direct impact on germplasm maintenance strategies and sampling numbers for utilization and study of collections. Cowpea is primarily an autogamous species though outcrossing does occur and rates up to 5% have been recorded in cultivated species. In order to assess the level of inbreeding and heterogeneity within the cowpea collection at IITA we conducted a study sampling 100 landraces and assessing ten plants per landrace, inbreeding levels and diversity were assessed using SSR markers. Analysis of the intra accession variation indicated that inbreeding in the cowpea accessions studied was not as complete as may have previously been assumed. In addition, it was observed that analysis of 5 plants per accession would provide a more precise measure of diversity than the one typically used. However, while increasing the numbers of plants genotyped per accession in would give a more accurate representation of diversity, the contribution of this information to our knowledge would be extremely slight and questionably inefficient.